Alzheimer's disease pathology explains association between dementia with Lewy bodies and APOE‐ε4/TOMM40 long poly‐T repeat allele variants - Inga Prokopenko; Gentaro Miyakawa; Bang Zheng; Jani Heikkinen; Daniela Petrova Quayle; Chinedu Udeh‐Momoh; Annique Claringbould; Juliane Neumann; Hazal Haytural; Marika A. Kaakinen; Elena Loizidou; Esther Meissner; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction The role of TOMM40‐APOE 19q13.3 region variants is well documented in Alzheimer's disease (AD) but remains contentious in dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD). Methods We dissected genetic profiles within the TOMM40‐APOE region in 451 individuals from four European brain banks, including DLB and PDD cases with/without neuropathological evidence of AD‐related pathology and healthy controls. Results TOMM40‐L/APOE‐ε4 alleles were associated with DLB (ORTOMM40‐L = 3.61; P value = 3.23 × 10−9; ORAPOE‐ε4 = 3.75; P value = 4.90 × 10−10) and earlier age at onset of DLB (HRTOMM40‐L = 1.33, P value = .031; HRAPOE‐ε4 = 1.46, P value = .004), but not with PDD. The TOMM40‐L/APOE‐ε4 effect was most pronounced in DLB individuals with concomitant AD pathology (ORTOMM40‐L = 4.40, P value = 1.15 × 10−6; ORAPOE‐ε4 = 5.65, P value = 2.97 × 10−8) but was not significant in DLB without AD. Meta‐analyses combining all APOE‐ε4 data in DLB confirmed our findings (ORDLB = 2.93, P value = 3.78 × 10−99; ORDLB+AD = 5.36, P value = 1.56 × 10−47). Discussion APOE‐ε4/TOMM40‐L alleles increase susceptibility and risk of earlier DLB onset, an effect explained by concomitant AD‐related pathology. These findings have important implications in future drug discovery and development efforts in DLB.